Shikonin induces apoptosis and autophagy via downregulation of pyrroline-5-carboxylate reductase1 in hepatocellular carcinoma cells. Issue 3 (1st March 2022) - Zhang, Junli; Shang, Ling; Jiang, Wendi; Wu, Wenjuan
ABSTRACT: Shikonin(SK) is a natural small molecule naphthoquinone compound, which has anti-cancer activity in various human malignant tumors. Pyrroline-5-carboxylate reductase 1(PYCR1) is involved in tumorigenesis and regulates various cellular processes, including growth, invasion, migration, and apoptosis. However, the effect of SK and PYCR1 on apoptosis and autophagy in hepatocellular carcinoma are unclear. Our goal is to determine the internal molecular mechanism of the interaction between SK and PYCR1 and its role in the occurrence and development of liver cancer. The CCK8 assay, wound healing assay, and transwell assays show that SK and siPYCR1(gene silence PYCR1) inhibited the malignant phenotype of HCC cells, including cell viability, colony formation, migration, and invasion, respectively. The flow cytometry assays and immunofluorescence show that SK and siPYCR1 activated apoptosis and autophagy, respectively. SK induces apoptosis and autophagy in a dose-dependent manner. In addition, HCC cells were transfected with small interference fragment PYCR1 siRNA to construct siPYCR1 and SK single treatment group and co-treatment group to verify the interaction between SK and PYCR1. The Western blot identified that PI3K/Akt/mTOR signal pathway protein expression was significantly downregulated in HCC cells treated with SK and siPYCR1 together. Collectively, SK may induce apoptosis and autophagy by reducing the expression of PYCR1 and suppressing PI3K/Akt/mTOR. Thus, SK may be a promising antineoplastic drug in Hepatocellular carcinoma (HCC). SK downregulating PYCR1 might supply a theoretical foundation for the potential therapeutic application in hepatocellular carcinoma. Graphical abstract: uf0001